Conservation of nature - Duffey, Eric (London : Collins, 1970)
Describes how man through farming, industry, clearance of forests, and population growth began to change the earth and bring about critical shortages of natural resources.
Bibliography: p. 126.
Keywords: Conservation of natural resources -- Juvenile literature